(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The nexus between political influence, corruption, and governance failures within law enforcement and the criminal justice system is a classic example of the government not being strong but fat. Corruption is a key focus of how political power and vested interests manipulate law enforcement policies, criminalising specific activities while safeguarding influential minority groups. The analysis reveals the symptoms of undetected shady corrupt public officials and lobby groups in establishing police protection rackets, creating a cycle of corruption that benefits various stakeholders and sustains the status quo. Token interventions, such as occasional police raids or prosecutions, are shown to be superficial efforts aimed at placating public concerns without effectively addressing the entrenched corruption. The ever-mounting corruption cases and numbers detail how the criminal justice system’s resources are hypnotised. This article further examines the role of oversight bodies like the Civilian Secretariat for Police and the Portfolio Committee on Police in curbing corruption within the South African Police Service (SAPS). However, it finds that political interference, exemplified by cases involving high-ranking officials, continues to impede monitoring efforts. This underscores the broader implications of corruption, including threats to national security, economic instability, and deepening social inequality. It concludes by advocating for enhanced oversight and comprehensive reform to rebuild trust in governance and uphold the rule of law.